2021
DOI: 10.3389/fmicb.2021.646303
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biofilm Growth on 3D-Printed Materials

Abstract: Recent advances in 3D printing have led to a rise in the use of 3D printed materials in prosthetics and external medical devices. These devices, while inexpensive, have not been adequately studied for their ability to resist biofouling and biofilm buildup. Bacterial biofilms are a major cause of biofouling in the medical field and, therefore, hospital-acquired, and medical device infections. These surface-attached bacteria are highly recalcitrant to conventional antimicrobial agents and result in chronic infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 63 publications
2
30
1
Order By: Relevance
“…However, surface features, such as roughness or hydrophobicity, determined by the peg material itself, the additive manufacturing technology, or different coatings, led to differences in biofilm formation in a species-or strain-dependent manner. This is in agreement with a recent study (Hall et al, 2021) that suggested that antibacterial properties (e.g., incorporated metals), surface roughness, and hydrophobicity are the major determinants for biofilm growth by E. coli, P. aeruginosa, and Staphylococcus aureus on 3D-printed polylactic acid-based materials. The authors observed less biofilm growth on polymers filled with metals as well as on smoother and less hydrophobic surfaces; however, the strongest biofilm-forming strain in their study (P. aeruginosa) did not show the same correlation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, surface features, such as roughness or hydrophobicity, determined by the peg material itself, the additive manufacturing technology, or different coatings, led to differences in biofilm formation in a species-or strain-dependent manner. This is in agreement with a recent study (Hall et al, 2021) that suggested that antibacterial properties (e.g., incorporated metals), surface roughness, and hydrophobicity are the major determinants for biofilm growth by E. coli, P. aeruginosa, and Staphylococcus aureus on 3D-printed polylactic acid-based materials. The authors observed less biofilm growth on polymers filled with metals as well as on smoother and less hydrophobic surfaces; however, the strongest biofilm-forming strain in their study (P. aeruginosa) did not show the same correlation.…”
Section: Discussionsupporting
confidence: 93%
“…While we have shown that biofilms formed at 48 h indeed do not show any difference due to peg location, the biological variation (e.g., in terms of time to biofilm maturation) between replicates at earlier timepoints or when applying certain treatments can make the analysis more challenging compared with a situation where the same biofilm is analyzed before and after treatment, or at different timepoints. Although the validation of the system presented here was done on Enterobacteriaceae strains, we do not see any constraints in studying other microbes, as many have been shown to form biofilms on 3D-printed materials (Palka et al, 2020;Hall et al, 2021), and silicone devices (Singhai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the biofilm composition of Streptococci species are observed between the fourth and eighth hours of biofilm formation. The first colonizers correlate positively with each other and influence the colonization of bacteria of orange and red complexes during the development of peri-implantitis [17].…”
Section: Introductionmentioning
confidence: 96%
“…Therefore the demand for antimicrobial properties has also entered this 3D filament field. Some companies already sell filaments provided with antimicrobial properties [12].…”
Section: Introductionmentioning
confidence: 99%